ALPHA-GLUCOSIDASE INHIBITING ACTIVITY FROM THE MOST ACTIVE FRACTION OF CALOPHYLLUM TOMENTOSUM, WIGHT LEAVES - Elya, Berna; Puspitasari, Nuraini; Maharani, Fasya Hadaina (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study was to obtain the inhibitory concentration, 50% value from the most active fraction of methanolic extract of leaf Calophyllum tomentosum, Wight, and to identify the group of compounds contained in the most active fraction. Methods: The methanol extract was fractionated using the silica gel static phase, the n-hexane motion phase, ethyl acetate, and methanol enhanced by its polarity. Results: There were nine selected fractions tested in inhibitory activity using an enzyme activity inhibitory assay. Conclusions: The results showed the inhibition by the most active fraction is 51.288 Î¼g/mL; this fraction contains of flavonoid, saponin, and terpenoid.